2015
DOI: 10.4236/ijaa.2015.51005
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations and Spikes by the Torsind Registered and Their Impact on the Accuracy of G Measurement

Abstract: The article reports on the results of an analysis of the torsind behavior long-term observations. The torsind is a species of ultralight disc torsion balance. The data analysis showed that the signal recorded contains the 24-hour periodic component presumably associated with the Sun. Moreover, unpredictable strong impacts, forcing torsind disk to rotate in one or another direction, were revealed. Presumably the reason of these effects is the Sun. This indicates the existence of an unknown radiation that bears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These facts indicate the presence of previously unexplored space radiation component of non-electromagnetic nature, which carries a torque. This torque, previously titled T-momentum [20], may be perceived by mechanical systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These facts indicate the presence of previously unexplored space radiation component of non-electromagnetic nature, which carries a torque. This torque, previously titled T-momentum [20], may be perceived by mechanical systems.…”
Section: Discussionmentioning
confidence: 99%
“…This property is manifested not only at times of solar and lunar eclipses. Torsind "feels" the sunrise and sunset, clear responds to the so-called daily cycle [20]. August 2016 | Volume 3 | e2728…”
Section: Special Torsind Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Pugach [9] reported that an eclipse of the Sun happening in the other side of the planet creates observable variations on his balance. That aim the author to quantify that effect.…”
Section: The 2017 Total Eclipse Of the Sunmentioning
confidence: 99%
“…Hawking and Rayner express in [5] that per the Mach's principle, the "Local physical laws are determined by the large-scale structure of the universe". In addition, Pugach [6] reports extensive experimental work indicating that torsion balances are disturbed by the Sun's activity. The work reported in this paper will be limited to create the connection between a well-established theory and the experimental data available.…”
Section: Introductionmentioning
confidence: 99%